Study on prescribing pattern and drug interactions of dyslipidemic agents in a tertiary care hospital (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Dyslipidemia is one of the major contributors to atherosclerosis and coronary heart disease in our society.  Dyslipidemic drugs are widely used either for prophylaxis or treatment of dyslipidemia. HMG CoA reductase inhibitors (statins) are a widely used class of lipid lowering drugs, which are generally well-tolerated, with an acceptable side effect profile. They are the first line of therapy for lipid lowering and attaining ATP III goals.The objective of the study is to determine the prescribing pattern and drug interactions of dyslipidemic agents in the selected study population as per the inclusion criteria. A prospective observational study was conducted. The data was collected during regular ward rounds and was analysed. The prevalence of CVD was significantly higher (62%) in the study population. The majority of patients 144 (96%) were receiving lipid lowering therapy with statins and 5 (3.33%) patients were on combination therapy including a statin and fibrate and 1 (0.67%) patient was on fibrate alone. Atorvastatin is majorly prescribed in 137 (91.95%) patients followed by rosuvastatin in 12 (8.05%) patients. The drug interaction between dyslipidemic agents were analysed and categorized, there were 2 (1.55%) major, 125 (96.90%) moderate and 2 (1.55%) minor possible drug-drug interactions were found.The results reveal that statins were prescribed more compared to other classes of dyslipidemic agents. Atorvastatin was the most commonly prescribed statin in the study site for the treatment of dyslipidemia. Atorvastatin utilization is significantly higher than rosuvastatin, even though recent studies describes that rosuvastatin is more efficacious and safe when compared to atorvastatin. Further studies may justify effectiveness of various statins.